2015
DOI: 10.1242/bio.013128
|View full text |Cite
|
Sign up to set email alerts
|

AINTEGUMENTA and the D-type cyclin CYCD3;1 regulate root secondary growth and respond to cytokinins

Abstract: Higher plant vasculature is characterized by two distinct developmental phases. Initially, a well-defined radial primary pattern is established. In eudicots, this is followed by secondary growth, which involves development of the cambium and is required for efficient water and nutrient transport and wood formation. Regulation of secondary growth involves several phytohormones, and cytokinins have been implicated as key players, particularly in the activation of cell proliferation, but the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…ANT encodes the AP2‐like ethylene‐responsive transcription factor ANT (Elliott, ; Nole‐Wilson and Krizek, ), the absence of which is connected with precocious termination of cell proliferation (Mizukami and Fischer, ). CKs were found to regulate the expression of ANT and CYCD3 that further independently regulate cell division during secondary growth of Arabidopsis roots (Randall et al ., ). We found that CK deficiency leads to a reduction in ANT transcript levels in the early proliferating leaf 3, and could lead to the loss of the cellular ability to maintain division competence and, consequently, could induce an early exit from cell proliferation, as predicted in Werner et al .…”
Section: Discussionmentioning
confidence: 97%
“…ANT encodes the AP2‐like ethylene‐responsive transcription factor ANT (Elliott, ; Nole‐Wilson and Krizek, ), the absence of which is connected with precocious termination of cell proliferation (Mizukami and Fischer, ). CKs were found to regulate the expression of ANT and CYCD3 that further independently regulate cell division during secondary growth of Arabidopsis roots (Randall et al ., ). We found that CK deficiency leads to a reduction in ANT transcript levels in the early proliferating leaf 3, and could lead to the loss of the cellular ability to maintain division competence and, consequently, could induce an early exit from cell proliferation, as predicted in Werner et al .…”
Section: Discussionmentioning
confidence: 97%
“…On a shift to SDs, FT expression is repressed, leading to the downregulation of LAP1 and AIL expression. As AIL1 controls the expression of key cell cycle regulators, for example D‐type cyclins (Karlberg et al ., ; Randall et al ., ), its downregulation results in the suppression of cell cycling and, hence, growth cessation. Thus, according to this model, SDs essentially induce the removal of a growth‐promotive signal rather than the generation of a growth inhibitor.…”
Section: How Does Photoperiod Control Developmental Transitions?mentioning
confidence: 99%
“…Among them, Module #105, involved in lateral root development, had 7 predictor TFs, LBD29, LBD18, LBD16, PUCHI, GATA23, LBD17, and WOX11, all of which except LBD17 have been shown to be regulators of lateral root development ( Figure 4C) (21,22). Module #65, for xylem development, had 10 predictor TFs, 7 of which are known modulators (MP, WOX4, ATHB8, TMO5, T5L1, VND5, ANT) of xylem or vascular development (23,24) and the other 3 could be potential regulators ( Figure 4D). On the other hand, all identified predictors for Module #11, functioning in secondary cell wall biogenesis, are known regulators of secondary cell wall biosynthesis, including SND1, SND2, SND3, VND4, VND6, MYB46, MYB103, MYB83, IRX11, NST2, LBD15 and AtC3H14 ( Figure 4E) (5,(25)(26)(27)(28).…”
Section: Transcriptional Regulators Revealed By the Predictormentioning
confidence: 99%